We Still Have to Eat: Communication Infrastructure and Local Food Organizing as Public Health Responses to COVID-19 in Greensboro, North Carolina - LeGreco, Marianne; Palmer, Jasmine; Levithan, Marianna (Frontiers in Communication, 2021)
Food insecurity remains a pervasive and persistent social justice concern, both locally and globally - a concern that was heightened during the COVID-19 pandemic. This essay focuses on three short case studies around local food organizing, communication, and community in Greensboro, NC. Partners across three separate but related interventions leveraged their community and communication resources through listening sessions, surveys, and stories to ensure that individuals and families could continue to access food during the uncertainty of the COVID-19 pandemic. By offering these case studies as an example of organizing (and reorganizing) during COVID-19, the analysis also opens up a conversation about power, resistance, and change at the intersections of poverty and access. Scholarly discussions of food insecurity continue to reinforce the need to address both food access and poverty in attempts to build resilient food systems. We take a community-engaged approach that emphasizes the importance of communication infrastructure to illustrate both the simple and mundane resources as well as the creative and innovative interventions that communities and their partners implemented during the initial onset of COVID-19 in the United States.